Experiences of receiving cognitive analytic therapy for those with complex secondary care mental health difficulties. Issue Volume 94:S1(2021)Special Issue (23rd January 2021) - Balmain, Nadia; Melia, Yvonne; John, Christopher; Dent, Helen; Smith, Karen
Abstract : Objectives: Service users with complex mental health difficulties are more difficult to engage in treatment and drop‐out rates are higher, resulting in poorer clinical outcomes. Cognitive analytic therapy (CAT) is widely applied to service users with complex needs and shows promise in terms of engagement and outcomes. The aim of the present study was to examine the 'lived experience' of service users who have been retained in a full course of CAT treatment to provide important insights to why CAT seems to be an engaging psychotherapy, to inform future CAT delivery and practice with clients with complex needs. Method: Semi‐structured interviews were undertaken with six service users aged between 25 and 47 years who had accessed secondary mental health care services and had received an average of 24 sessions of CAT. Transcripts were analysed using interpretative phenomenological analysis (IPA). Results: The analysis yielded three superordinate themes with subthemes within these. The first superordinate theme referred to changes due to CAT (e.g., insight, tools to cope). The second theme referred to strong emotions evoked by CAT (e.g., feeling frustrated, scared, and upset). The final theme concerned the process of CAT (e.g., endings and therapeutic relationship). Conclusions: Whilst service users appeared to develop increased insight and acquire skills, there was variance in experiences of sustained and meaningful change post‐therapy. The findings suggest adaptations may be required with these service users such as delivering the sequential diagrammatic reformulation (SDR) in a hopeful way and addressing systemic barriers to 'exits' being made. Practitioner points: Overall, service users with complex mental health difficulties describe benefitting from CAT, identifying improved insight and the acquisition of tools to cope. However, therapists need to be attuned to the potential fragility of service users and risk of negative affect, particularly during the reformulation phase. Consideration of delivering the SDR in a hopeful way may be therapeutic. Systemic factors such as service users being pulled to maintain the status quo in their relationships, and lack of support for or resistance to change by important others limit service users from availing of 'exits' from problem procedures. This implicates the need for more attention to systemic and possibly multi‐agency working with this group of service users.